Assistance in agricultural waste fermentation technology in Krueng Kalee Village, Darussalam Sub-District, Aceh Besar [Pendampingan teknologi fermentasi limbah pertanian di Gampong Krueng Kalee Kecamatan Darussalam Aceh Besar] - Masda Admi; A Azhari; Hendri Syah (The Institute for Research and Community Services (LPPM) Universitas Syiah Kuala (USK), 2024)
Agricultural waste holds significant potential as a source of animal feed and liquid organic fertilizer through the application of fermentation technology. The types of agricultural waste that can be utilized include water spinach leaves, sweet potato leaves, and spinach leaves. The utilization of these wastes not only adds value but also contributes to enhancing the economic independence of communities. Using waste as animal feed offers a sustainable alternative, especially during dry seasons and planting periods, with the potential for higher nutritional content following the fermentation process. The aim of this community service initiative is to educate the public about the types of agricultural and plantation waste that can be used as animal feed, as well as the risks to be avoided related to the effects of fermented feed. Additionally, the program involves training the community in the application of fermentation technology on rice straw, vegetable waste, and cassava leaves, utilizing microbial starters derived from the rumen of goats and cows that have adapted to cyanide toxins. The methods employed in this initiative include outreach and hands-on practice in the production of fermented feed and liquid organic fertilizer. The results indicate a high level of enthusiasm among community members regarding the dissemination of information on utilizing agricultural waste as materials for fermented feed and liquid organic fertilizer, as well as an increased awareness of the importance of environmental preservation surrounding residential and agricultural areas. In conclusion, this initiative has fostered a commitment from partners to independently implement fermentation processes, along with a hope for the continuation of further community service programs focused on the application of technology to enhance the economic conditions of farmers and livestock farmer.